Analysis of tourism indicators in function of tourist offer enrichment in Mecedonia - Deja Nakovski; Ace Milenkovski; Mijalce Gjorgievski (UTMS Journal of Economics, 2016)
The tourism in Macedonia according to relevant statistical indicators still is or is longer on low (unsatisfactory) level, which is expressed both by the number of tourists visiting the country and by the number of realized overnights by tourists. Another feature of tourism in Macedonia is its emphasized seasonal character, which the authors considered as a negative trait. To improve the current situation in the tourism industry in Macedonia it is necessary to improve and enrich the tourist offer. According to the authors one of the best ways to improve the quality of the tourist offer is through actualization, promotion and strategic management of the events in function of tourism. The aim of the paper is to show how through correct strategy and event management can significantly improve the situation in tourism on the basis of all the above mentioned indicators, especially when it comes to the seasonal nature of tourism and to make certain dispersion of tourist movement beyond the traditional tourist destinations in the country.
Keywords: Q26; L83; 330; events; development; tourism product; dispersion of tourists